Le Mot juste: An interview with Howard Jacobson by Anne-Marie Picard. Issue 5 (20th October 2017) - Picard, Anne-Marie; Jacobson, Howard
ABSTRACT: Anne-Marie Picard interviews British novelist, Booker Prize winner, and journalist Howard Jacobson about his satirical novel, Pussy (Penguin, 2016). In the shocking aftermath of Trump's election, with as much Dickens as Swift, and memories of Rabelais, the novelist writes "in a fury of disbelief, " wanting "a fast attack with no quarter given. No quarter given, not only to Fracassus, " the Trump character, "but the world in which his rise was made possible."